Joint Vehicular and Static Users Multiplexing Transmission With Hierarchical Modulation for Throughput Maximization in Vehicular Networks - Gao, Qian; Lin, Siyu; Zhu, Gang (IEEE transactions on intelligent transportation systems, 2020)
With the rapid development of intelligent transportation system (ITS), increasing the throughput of all kinds of users in the mobile communication network is a pressing problem. We consider there are two types of users, i.e. vehicular users (VUs) and static users (SUs), in a vehicular communication network. Since the channel characteristics of VUs and SUs are different, designing a multi-user multiplexing transmission strategy to provide an efficient and reliable transmission for two types of users is quite challenging. We propose a dynamic cross-layer transmission strategy with joint admission control, user association and resource allocation to increase the total throughput of VUs and SUs while satisfying the different quality of service (QoS) requirements. First, we formulate a throughput utility maximization problem subject to the QoS and maximum transmit power constraints. Second, with the help of Lyapunov optimization theory, the problem can be decomposed into three subproblems including traffic admission control, user association and resource allocation. Third, a novel robust resource allocation scheme with discrete-rate hierarchical modulation (HM) is designed for the reliable multiplexing transmission of two types of users. In addition, an optimal algorithm and a low complexity suboptimal algorithm are presented to solve the user association subproblem. For two types of users, comparing with uniform modulation schemes, the proposed transmission strategy with HM scheme can improve the throughput by more than 15%.